Reconstruction of the anterior abdominal wall using a myocutaneous flap from the tensor fasciae latae muscle in a patient with squamous cell carcinoma of the skin - Sioch, Natalia; Krotofil, Julia; Kołpaczyńska, Sylwia (Quality in Sport, 2025)
The present study reports the case of a 59-year-old female patient admitted to the department due to advanced skin cancer in the lower abdominal region extending to the peritoneum. The patient was qualified for tumor resection with simultaneous reconstruction using flap surgery techniques, employing a tensor fasciae latae muscle flap. The intervention involved wide tumor resection aimed at maximizing the likelihood of achieving oncological radicality. Reconstruction was carried out using a propeller flap from the tensor fasciae latae muscle and a rotational musculocutaneous flap based on the external oblique muscle. The procedure concluded with a skin graft from the thigh, which covered the remaining tissue defect after flap harvesting. The described reconstruction technique was carefully planned, considering the defect's characteristics and the patient’s condition, highlighting the importance of individualized approaches in plastic surgery. This case illustrates the complexity of surgical procedures in cancer patients and the significance of avoiding foreign materials in the context of chronic infections.